HUBUNGAN GANGGUAN FUNGSI TIROID TERHADAP KADAR LDL-KOLESTEROL - Arie, Gristine Arie (Jurnal SainHealth, 2021)
Thyroid hormone has an important role in various body metabolic processes (proteins, carbohydrates, lipids) and physiological activities in almost all organs of the human body. Deficiency or excess of thyroid hormone can interfere with the metabolism of the body's organs. Hypothyroidism is a condition in which thyroid hormone in body tissues decreases, while hyperthyroidism is an excess of thyroid hormone circulating in the circulation due to a hyperactive thyroid gland. It also exerts a specific effect on lipid metabolism. In disorders of thyroid function, lipid metabolism will be disrupted, causing risk factors for cardiovascular disease, one of which is atherosclerosis (blockage/plaque) in blood vessels. In the case of hypothyroidism, there is often an increase in LDL-cholesterol levels, while in hyperthyroidism, there is often a decrease in LDL-cholesterol levels. Diagnosis of thyroid function disorders FT4 and TSH laboratory tests become the standard for establishing an appropriate thyroid diagnosis. This study aims to determine the relationship between thyroid disorders, especially FT4 and TSH, on LDL-cholesterol levels. The study used descriptive data taken at the Pramita Clinical Laboratory, Surabaya in January – December 2019. The data collected came from the medical records of patients who did FT4, TSH and LDL-Cholesterol examinations as many as 80 people consisting of 22 men and 58 women with a range of age 22-81 years. From the data, the characteristics of the sexes are male (27.5%), female (72.5%). In hyperthyroidism, the mean levels of TSH (0.0612 IU/mL), FT4 (1.53 ng/dl), LDL-Cholesterol (99 mg/dl) while hypothyroidism mean TSH levels (17.427 IU/mL), FT4 (0 ,92 ng/dl), LDL-Cholesterol (130 mg/dl). Bivariate correlation analysis was used to see the relationship between levels of FT4 with LDL-cholesterol and TSH with LDL-cholesterol. From the data obtained, there is a positive correlation between TSH and LDL-cholesterol levels in hypothyroid disorders and a negative correlation between FT4 and LDL levels in hyperthyroidism. In this study, the results showed that thyroid function disorders had an effect on increasing/decreasing LDL cholesterol levels. Keywords : Free T4, TSH, LDL-cholesterol, hypothyroid and hyperthyroi